Inflammation mediates the adverse effects of urinary phthalate exposure on metabolic disease risk: Results from NHANES 2005–2016 - Chenyang Gu; Teng Yao; Chenxian Dong; Zuhai Chen; Wanting Wei; Xiaoju Li; Qiang Niu; Yizhong Yan; Yunhua Hu (Ecotoxicology and Environmental Safety)
Background: Phthalates are a category of chemicals commonly utilized in various industrial applications and everyday products. Their associations with health issues remains a significant concern. Although some studies have suggested associations between phthalates and metabolic diseases, the current understanding of the associations is still limited, especially the lack of effects of mixed exposure. Methods: This cross-sectional study included information from 9217 participants in National Health and Nutrition Examination Survey (NHANES) from 2005 to 2016. Multivariate logistic regression was used to explore the associations between single phthalate exposure and obesity and its complications. Weighted quantile sum (WQS) regression and Quantile G-Computation (Qgcomp) models were used to further analyze the associations between mixed phthalate exposure and obesity and its complications. Mediated analysis was used to explore the mediating role of immune cells in the relationship between phthalate exposure and obesity and its complications. Results: MiBP, MCOP and MBzP were associated with an increased risk of obesity. MiBP and MCOP were associated with an increased risk of abdominal obesity. MCNP, MCOP, MEHHP, MEOHP and MECPP were positively associated with T2DM. Mixed phthalate exposure was positively associated with obesity and T2DM. Monocytes mediated the effects of MiBP, MEHP and MBzP on obesity, explaining 7.94 %, −2.32 % and 6.69% of the total effect, respectively. Conclusions: This study revealed a significant association between mixed phthalate exposure and obesity and its complications, underlining the importance of considering the interactions of these compounds. The synergistic effects of multiple phthalates may exacerbate health risks.